Implemetasi metode WaterFall Pada Sistem Informasi Inventori Perdana Cellular Group - Saputro, Arief; Syabibi, Dandan Aly; Nugraha, Rizky Aditya; Andhyka, Awang; Mu’min, Syahri (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
Information and communication technology is currently developing very rapidly, especially in terms of data collection of goods and sales which greatly facilitates and efficiency in processing. Therefore, the prime cellular group in stock inventory that still uses conventional methods has used a web-based inventory information system by applying the waterfall method. The author performs needs analysis, system design to system testing. The system built uses the PHP programming language and the data storage system uses MYSQL. This built-in system makes it easier to process inventory, stock management and sales.